2015
DOI: 10.1055/s-0035-1546272
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of Essential Oils against Fusarium Keratitis Isolates

Abstract: The present study was carried out to investigate the antifungal effects of Cinnamomum zeylanicum, Citrus limon, Juniperus communis, Eucalyptus citriodora, Gaultheria procumbens, Melaleuca alternifolia, Origanum majorana, Salvia sclarea, and Thymus vulgaris essential oils against Fusarium species, the most common etiologic agents of filamentous fungal keratitis in South India. C. zeylanicum essential oil showed strong anti-Fusarium activity, whereas all the other tested essential oils proved to be less effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Assays with Saccharomyces cerevisiae yeast cells in the presence of the essential oils obtained from fruit and leaves did not show toxicity levels near the LD 50 found in our study. This seems confusing given the strong antifungal activity of essential oils, such as of Cinnamomum zeylanicum on the pathogenic filamentous fungus Fusarium keratitis (Homa et al 2015), or of Melaleuca alternifolia on the fungus Botrytis cinerea (Yu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Assays with Saccharomyces cerevisiae yeast cells in the presence of the essential oils obtained from fruit and leaves did not show toxicity levels near the LD 50 found in our study. This seems confusing given the strong antifungal activity of essential oils, such as of Cinnamomum zeylanicum on the pathogenic filamentous fungus Fusarium keratitis (Homa et al 2015), or of Melaleuca alternifolia on the fungus Botrytis cinerea (Yu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of its compounds could have anti-cancer activities [49]. A study on the effect of Cinnamomum verum essential oil on Fusarium strains responsible for keratitis in humans was conducted and showed an efficacy at a concentration between 31.25 and 500 μg/mL, depending on the strain studied [50].…”
Section: The Main Essential Oils With Antifungal Activitymentioning
confidence: 99%
“…The Pelargonium graveolens essential oil has been used due to its hypoglycemic and antioxidant [12] properties, and exhibits also antifungal and insecticidal activities against Rhizoctonia solani and Rhysopertha dominica, respectively [13]. The use of Citrus aurantium essential oil by Homa et al [14] revealed the antifungal activity against different isolates of Fusarium keratitis, antibacterial activity against Vibrio species [15], as well as insecticidal activity against Aedes aegypti and Anopheles dirus [16]. As mentioned above, there are many properties of these essential oils, but there are only few studies on their acaricidal effects despite the great interest on finding alternative control methods.…”
Section: Introductionmentioning
confidence: 99%